Learning Process of Communication Arts’ Students in Creating Local Cooking Video Materials - Kanoknet Pinitdankang,; Araya Lanumtieng,; Theeranan Khantee,; Phakwarin Manasirisit,; Wijit Sirigit, (Journal of Educational Issues, 2024)
This project examines the students learn about producing local food videos. The 3-step learning process was conducted by each video was created from 1 piece per content with a 20-minute movie using a step-by-step learning procedure. Three pre-productions: pre-, pre-, and post-production. The data study demonstrated the local cooking media’s reliance on visual, auditory, and content features by having students create local cookery videos as part of their learning process. Then, video materials were implemented and asked local community members towards its useful and appropriateness. The findings demonstrated that the list satisfied the respondents’ questions. The most visible feature has a dependability degree of satisfaction average of 4.76, making it the most satisfied.